Improving the Ability to Present Information in the Form of Writing Stories Through Interactive Learning Media - Idha Rachmawati; Esti Untari; Sri Kustiyah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
Writing stories can start when students are in elementary school. Through story writing activities students can express their feelings, ideas, and ideas to others. Based on the results of interviews and observations conducted on January 20, 2021, the 5th grade homeroom teacher of SDN 5 Sudimoroharjosiswa felt bored in online learning during the pandemic. This can be seen from the students' writings that do not match the information. The writing of stories that do not match this information can be seen from one of the students who did not write down sports activities where there are pictures of people who are exercising. This study aims to determine the ability of students to present information in the form of stories through interactive image media based on thinglinks for grade 5 students at SDN 5 Sudimoroharjo, Nganjuk Regency. Based on the results of research on the use of interactive image media based on thinglink in Indonesian language learning, the material for retelling the sequence of events in fictional texts according to the background of the story has been carried out, it can be concluded that: (1) The implementation of learning using interactive image media based on thinglink is carried out according to the steps of learning activities which uses the project based learning model very well so as to increase the activities of teachers and students. This is evidenced by the increased activity of teachers and students in cycle I to cycle II. The average percentage of teacher activity in the first cycle is 82.85% with good criteria increasing to 10.01% to 92.86% with very good criteria in the second cycle. While the average student activity from the first cycle is 77, 86% with sufficient criteria increased to 11.43% to 89.29% with good criteria in cycle II. (2) The application of learning using interactive image media based on thinglinks can improve the ability of V SDN 5 Sudimoroharjo students, Nganjuk Regency, in retelling the sequence of events in fictional texts according to the background of the story. This is evidenced by the increase in student learning outcomes when in the skill aspect with the average value in the first cycle of 74 increasing to 89.5 in the second cycle. In addition, the percentage of student learning completeness also increased starting in the first cycle, namely 60.71% with less criteria, increasing by 39.29% to 100% with very good criteria in the second cycle. For teachers, it is recommended that if doing learning using interactive image media based on thinglinks, they should do a trial before being used by students.